Pengembangan Strategi Pemasaran untuk Meningkatkan Jumlah Siswa di Sekolah Dasar Negeri No 173634 Porsea - Rohani Sijabat; Rinciani Telaumbanua; Hiskia Maruli Siregar; Joel Ferdinan Siagian; Wisman Berkat Zai; Parsaoran Silalahi (Merwinspy Publisher, 2025)
The purpose of this service is to create a successful marketing strategy to increase the marketing results of student numbers at State Elementary School (SDN) No. 173634 Porsea. This has led to a decline in student numbers in recent years. Education marketing is essential to build a positive image of the school and stimulate community interest. This service activity was carried out using interviews and observations. Interviews were conducted to obtain more in-depth information. Observations were made to obtain more accurate and detailed information, by observing activities carried out by students of Public Elementary School No. 173634 Porsea, such as teaching and learning activities, extracurricular activities, and other activities. The results showed that effective marketing strategies include improving the quality of education, expanding collaboration networks with parents and communities, and promoting social media. Although the number of students decreased, the efforts proved to increase positive results. The school has made several efforts to improve its image and the quality of education which has started to get positive attention from the community. The smaller decrease shows that the efforts made to attract students are starting to show results, indicating that steps have been taken by the school to improve the quality of education and improve the school's image in the eyes of the community. Schools can promote in any way that emphasizes the importance of marketing in building a positive image and increasing community interest.